2005
DOI: 10.1037/0003-066x.60.5.410
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychology Progress: Empirical Validation of Interventions.

Abstract: Positive psychology has flourished in the last 5 years. The authors review recent developments in the field, including books, meetings, courses, and conferences. They also discuss the newly created classification of character strengths and virtues, a positive complement to the various editions of the Diagnostic and Statistical Manual of Mental Disorders (e. g., American Psychiatric Association, 1994), and present some cross-cultural findings that suggest a surprising ubiquity of strengths and virtues. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

108
3,382
21
343

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,382 publications
(3,854 citation statements)
references
References 31 publications
108
3,382
21
343
Order By: Relevance
“…They found that when individuals performed several random acts of kindness on one day each week, their happiness improved. Seligman, Steen, Park, and Peterson (2005) reported a series of happiness interventions that were implemented via the Internet. They found that several of these interventions led to changes in happiness that persisted for at least six months.…”
Section: Implications Of the Revised Modelmentioning
confidence: 99%
“…They found that when individuals performed several random acts of kindness on one day each week, their happiness improved. Seligman, Steen, Park, and Peterson (2005) reported a series of happiness interventions that were implemented via the Internet. They found that several of these interventions led to changes in happiness that persisted for at least six months.…”
Section: Implications Of the Revised Modelmentioning
confidence: 99%
“…Several studies show that reflection about positive events leads to better well-being and less exhaustion (Bono et al, 2013;Chan, 2011;Seligman et al, 2006;Seligman et al, 2005).…”
mentioning
confidence: 99%
“…In terms of interventions, studies have demonstrated that positive reflection reduces depressive symptoms (Seligman et al, 2006;Seligman et al, 2005) and enhances positive affect (Chan, 2011). Positive reflection about work-related events is associated with less stress and fewer health complaints (Bono et al, 2013).…”
mentioning
confidence: 99%
“…The influence of positive psychology in the construction of these specific interventions is very significant which zeroed in on optimizing character strengths more than alleviating symptoms. Seligman, Steen, Park, and Peterson (2005) tested the efficacy of positive psychological interventions in increasing happiness and reducing depression levels of the subjects through online intervention strategies. The gratitude visit exercise yielded the largest effect size in enhancing happiness indices of the subjects during the first month of the study.…”
Section: Conceptual Frameworkmentioning
confidence: 99%